Immunotherapy for Metastatic Melanoma with Right Atrial Involvement in a Patient with Rheumatoid Arthritis - Zachary Benson; Sarah Gordon; Patricia Nicolato; Andrew Poklepovic (Case Reports in Oncological Medicine)
Prognosis for metastatic melanoma has improved significantly with the use of immune checkpoint inhibitors. Given improvements in survival, aggressive surgical treatment may be considered in patients with life-threatening complications from their disease that would not otherwise be considered in advanced disease. Patients with preexisting autoimmune diseases or prior immune-related adverse events from therapy are largely excluded from clinical trials. Concerns exist that immunotherapy in these patients could worsen autoimmune disease or increase the risk of developing additional immune-related adverse events on therapy. We present a case of a patient with rheumatoid arthritis that presented with obstructive heart failure secondary to melanoma that had metastasized to the right atrium. After aggressive surgical resection to stabilize him from his life-threatening heart failure, he was treated with ipilimumab, which was stopped due to an immune-related adverse event. He was then started on pembrolizumab and had a durable response to therapy. Aggressive surgical treatment should be considered in patients with a cancer that may respond to immunotherapy. Furthermore, some patients with preexisting autoimmune disease may be safely treated with checkpoint inhibition therapy, and patients with a severe immune toxicity from one class may successfully be treated with an alternate class.